The role of sexist discrimination in adult women's identity development - Anthis, Kristine (Sex Roles, 2002)
The purpose of the current study was to examine the relationship between sexist discrimination and identity development in a sample of adult women. Participants completed a scale to indicate the extent to which sexist events had occurred in their lives and a measure of identity at 2 different data collection periods that spanned approximately 5 months. The results indicated that sexist events reported to occur within the last year at the first data collection period significantly predicted identity scores at the second data collection period. These findings are discussed in terms of how sexist discrimination may play a role in adult women's identity development and in terms of the additional psychometric data that supports the validity of the measure of sexist discrimination.
Keywords: dept.psy; identity; sexist discrimination; women

Winning friends and influencing peers: Strategies of peer influence in late childhood - Hawley, Patricia H; Little, Todd D; Pasupathi, Monisha (International Journal of Behavioral Development, 2002)
We divided children (N = 719, grades 3-6) into five control types based on the degree to which they reported employing prosocial (indirect, cooperative) and coercive (direct, hostile) strategies of control (prosocial controllers, coercive controllers, bistrategic controllers, noncontrollers, and typicals). We tested for differences across the five types on personal characteristics, friendship motivations, wellbeing, and social integration, expecting specific patterns according to whether control is wielded, and whether coercive or prosocial behaviour (or both) is employed. Prosocial controllers revealed positive characteristics (e. g., social skills, agreeableness), intrinsic friendship motivations, and positive wellbeing. In contrast, coercive controllers revealed negative characteristics (e. g., hostility), extrinsic friendship motivations, and ill-being. Bistrategic controllers, as expected, reported the highest control, and revealed characteristics associated with both prosocial and coercive orientations. Noncontrollers, in contrast, did not report having these characteristics and felt the least effective in the peer group. Our evolutionary perspective offers unique predictions of how prosocial and coercive children are similar in terms of their instrumental goals and the consequences of using both strategies or neither.
Keywords: childhood; controlled study; cooperation; dept.psy; female; hostility; human; male; motivation; perception; personality test; persuasive communication; prediction; review; school child; social adaptation; social control; social interaction; sociology; wellbeing

George perkins marsh: prophet of conservation. - Martin, GJ (Professional Geographer, 2002)
Keywords: dept.psy; ⛔ No DOI found

Evidence against a constant-difference effect in concurrent-chains schedules - Mazur, James E (Journal of the Experimental Analysis of Behavior, 2002)
Savastano and Fantino (1996) reported that in concurrent-chains schedules, initial-link choice proportions remained constant as terminal-link durations increased as long as the subtractive difference between the two terminal-link schedules remained constant. Two experiments with pigeons were conducted to examine this constant-difference effect. Both experiments used equal variable-interval schedules as initial links. The terminal links were fixed delays to reinforcement in Experiment 1 and variable delays to reinforcement in Experiment 2. The durations of the terminal links were varied across conditions, but the difference between pairs of terminal links was always 10 s. In both experiments, preference for the shorter terminal link became less extreme as terminal-link, durations increased, so a constant-difference effect was not found, It is argued, however, that this choice situation does not provide clear evidence for or against delay-reduction theory versus other theories of choice.
Keywords: *Choice Behavior; *Motivation; *Reinforcement Schedule; Animals; Appetitive Behavior; Choice Behavior; Color Perception; Columbidae; Concurrent-chains schedules; Delay-reduction theory; Fixed delays; Key peck; Mental Recall; Motivation; Pigeons; Reinforcement Schedule; Variable delays; animal; appetite; article; color vision; comparative study; decision making; dept.psy; motivation; peer-reviewed; pigeons and doves; recall; reinforcement

Learning and behavior, 5th ed. - Mazur, James E. (2002)
Keywords: dept.psy

On the calamity theory of growth: the relationship between stressful life events and changes in identity over time - Anthis, Kristine (Identity, 2002)
Keywords: dept.psy

Social dominance and prosocial and coercive strategies of resource control in preschoolers - Hawley, P.H. (International Journal of Behavioral Development, 2002)
This study was designed to investigate the predictors of social dominance, the strategies children use to control resources (prosocial and coercive), and the associations between these strategies and measures of personality, social skills, and peer regard. A total of 30 preschoolers (ages 3-6) were rated by their teachers on social dominance. Based on these ratings, dominant children were paired with multiple subordinate children (i.e., block design; Kenny, 1990) and observed in a play situation designed to elicit resource control behaviour. As hypothesised, age and the surgency facet of extraversion predicted social dominance (but openness to experience did not). Furthermore, also as expected, both prosocial behaviour and coercive behaviour were related to resource control in the play situation. Last, both resource control strategies were associated with parent-rated social competence, but only coercive control was associated with positive peer regard (i.e., Likeability). Factors of personality (e.g. agreeableness, hostility) were not associated with either of the strategies. The utility of an evolutionary perspective to resource control and social competence is discussed.
Keywords: article; controlled study; dept.psy; female; group psychology; hostility; human; hypothesis; male; parent; personality; persuasive communication; play; prediction; preschool child; social adaptation; social behavior; social dominance; sociology; teacher

Concurrent-chain performance in transition: effects of terminal-link duration and individual reinforcers. - Mazur, James E (Animal learning & behavior, 2002)
Pigeons responded on concurrent-chain schedules with variable-interval initial links and equal delays as terminal links. The terminal-link delays were 1 sec in some conditions and 20 sec in other conditions. The percentages of reinforcers delivered for responses on the left key were 10%, 30%, 70%, or 90%, and this percentage was switched every five to nine sessions. The rate of change in the pigeons' response percentages after a switch was the same whether the terminal-link delays were 1 sec or 20 sec. Analysis of the effects of individual reinforcers showed that after a response on one key had been reinforced, response percentages on that key were higher for at least the next 100 responses. Small effects of individual reinforcers were evident after eight or nine additional reinforcers had been delivered. The effects of individual reinforcers were about equally large during times of transition and during periods in which overall response percentages were relatively stable.
Keywords: *Behavior, Animal; *Reinforcement, Psychology; Animalia; Animals; Columba; Columbidae; Random Allocation; Reaction Time; Reinforcement Schedule; animal experiment; article; conditioned reflex; conditioning; decision making; dept.psy; nonhuman; pigeon; reinforcement; task performance